Foreword to Art Music by Caribbean Composers Volume - De Lerma, Dominique-Rene (International Journal of Bahamian Studies, 2013)
Classical music has been traditionally not the domain of European musicians -- so we have been led to believe from publications, concerts, and text books. But it is not European property and was never claimed as such. This myth was perpetuated by the musicologists, who were also, not accidentally European.